Монгол орны голоцены үеийн байгаль орчны өөрчлөлт, хурдас хуримтлалын онцлог - Ц.Оюунчимэг; Ж.Батсүх (Geological Issues, 2023)
The investigations presented in this paper focus on the reconstruction of Holocene environmental change in Mongolia based on published paleoclimate records, including lake sediments, lake levels, pollen records and eolian sediment records. These data indicate that the early Holocene of Mongolia is characterized by increasing temperature and humidity. The mid Holocene is characterized by enhanced aridity, and during late Holocene humidity increased, evaporation decreased.